The use of social media for trip planning process: study of domestic tourists to Pahang - Fouzai @ Fauzi, Fatin Shafiqa; Abdul Latif, Samshul Amry (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh Campus, 2019)
In recent years, the use and reliance of social media by tourists have increased. Social media becomes the alternative to traditional media in the process of trip planning and travel decisions. This study aims to identify the influences of social media towards the trip planning process, which are pre, during, and post-trip among domestic tourists who visited the state of Pahang, Malaysia. This quantitative study identified the influences of social media on two areas, namely the trip planning process and the perceived level of trust. The data were collected using self-administered online questionnaires from domestic tourists who had visited the state within the past 12 months. The findings of this study indicate that the respondents use social media predominantly before the trip. The findings also show that travel information obtained through social media is perceived as trustworthy and reliable by the respondents. Future researchers may include larger samples from other demographic segments as well as the inclusion of other tourist classification